2018
DOI: 10.3390/s18020372
|View full text |Cite
|
Sign up to set email alerts
|

Human Identification by Cross-Correlation and Pattern Matching of Personalized Heartbeat: Influence of ECG Leads and Reference Database Size

Abstract: Human identification (ID) is a biometric task, comparing single input sample to many stored templates to identify an individual in a reference database. This paper aims to present the perspectives of personalized heartbeat pattern for reliable ECG-based identification. The investigations are using a database with 460 pairs of 12-lead resting electrocardiograms (ECG) with 10-s durations recorded at time-instants T1 and T2 > T1 + 1 year. Intra-subject long-term ECG stability and inter-subject variability of pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, the first attempt of using ECG for biometric purposes was presented by Biel et al in 1999 and [23,24]. Since then the researchers devoted much of their efforts to utilizing different methodologies to improve the ECG-based biometric performance [1,7,8,[25][26][27]. Different databases, both private and public, are used to evaluate the proposed approaches [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the first attempt of using ECG for biometric purposes was presented by Biel et al in 1999 and [23,24]. Since then the researchers devoted much of their efforts to utilizing different methodologies to improve the ECG-based biometric performance [1,7,8,[25][26][27]. Different databases, both private and public, are used to evaluate the proposed approaches [28].…”
Section: Introductionmentioning
confidence: 99%
“…Wübbeler et al [ 24 ] showed a method based on the distance between the first and second temporal derivatives of signals. Poree et al [ 25 ] used the maximal correlation coefficient applied over a 12-lead ECG, and a cross correlation of a 12-lead ECG was used for human verification [ 26 ] and identification [ 27 ]. Many researchers have suggested various sophisticated algorithms to classify the ECG signals, e.g., neural networks [ 20 , 28 , 29 ], independent component analysis [ 30 ], k-nearest neighborhood [ 31 , 32 , 33 , 34 ], and support vector machine [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biel et al's [12,13] works are considered the first attempt to use ECGs for biometric purposes, considering the biometric characteristics of measurability (ease with which the characteristic is obtained), permanence (no change over time), universality (possession of the characteristic by the individual), and uniqueness (no two individuals share the same characteristic) [14][15][16][17]. Since then, many researchers have proposed various ECG-based identification approaches [1,4,[18][19][20][21][22][23][24][25][26][27] using private and/or public databases [28,29].…”
Section: Introductionmentioning
confidence: 99%